2023
DOI: 10.1097/ms9.0000000000000257
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer presenting with acute pancreatitis complicated by Wernicke’s encephalopathy and a colonic fistula: a case report

Abstract: Introduction and Importance: This account details the case of a 39-year-old male patient who presented with acute necrotizing hemorrhagic pancreatitis. The comorbid conditions of Wernicke’s encephalopathy, and a pancreatic–colonic fistula developed during his care. This case is unique in that it illustrates the effects of these complications individually and through their interaction. Given that there are no firm guidelines regarding the nature and timing of interventions for a pancreatic–colonic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Tabriz et al reported attainment of physiological plasma levels only 12 months after surgery [8]. Several case studies seem to indicate that after the Whipple procedure, vitamin B1 deficiency can early lead to Wernicke's encephalopathy [17] and its supplementation is necessary to restore normal cognitive functions and prevent permanent brain damage [18]. As reported in a recent case study, Wernicke's encephalopathy is an uncommon condition due to thiamine deficiency and is very rarely associated with acute pancreatitis, occurring late in the PaC course [19].…”
Section: Vitamin B1mentioning
confidence: 99%
See 1 more Smart Citation
“…Tabriz et al reported attainment of physiological plasma levels only 12 months after surgery [8]. Several case studies seem to indicate that after the Whipple procedure, vitamin B1 deficiency can early lead to Wernicke's encephalopathy [17] and its supplementation is necessary to restore normal cognitive functions and prevent permanent brain damage [18]. As reported in a recent case study, Wernicke's encephalopathy is an uncommon condition due to thiamine deficiency and is very rarely associated with acute pancreatitis, occurring late in the PaC course [19].…”
Section: Vitamin B1mentioning
confidence: 99%
“…Preliminary studies suggest that thiamine deficiency may also be caused by fluorouracil-based chemotherapy [20], which is one of the most used chemotherapies for the treatment of PaC, even though these data still need to be confirmed. Furthermore, the preoperative nutrition status in pancreatoduodenectomy patients was reported to be significantly correlated with their prognosis [18].…”
Section: Vitamin B1mentioning
confidence: 99%